2017
DOI: 10.1128/genomea.01731-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Staphylococcus succinus 14BME20 Isolated from a Traditional Korean Fermented Soybean Food

Abstract: The complete genome sequence of Staphylococcus succinus 14BME20, isolated from a Korean fermented soybean food and selected as a possible starter culture candidate, was determined. Comparative genome analysis with S. succinus CSM-77 from a Triassic salt mine revealed the presence of strain-specific genes for lipid degradation in strain 14BME20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Among them, strain 14BME20 was selected as a starter candidate. Genomic analysis confirmed that strain 14BME20 did not contain any of the known S. aureus virulence factor-encoding genes but did carry strain-specific genes for lipid degradation, which may contribute to the production of volatile compounds (Jeong and Lee, 2017). Staphylococcus succinus isolates from doenjang, a highsalt-fermented soybean product, did not exhibit hemolysis (Jeong et al, 2016a) and attempts to amplify enterotoxin genes were unsuccessful (unpublished results).…”
Section: Staphylococcus Succinusmentioning
confidence: 95%
See 2 more Smart Citations
“…Among them, strain 14BME20 was selected as a starter candidate. Genomic analysis confirmed that strain 14BME20 did not contain any of the known S. aureus virulence factor-encoding genes but did carry strain-specific genes for lipid degradation, which may contribute to the production of volatile compounds (Jeong and Lee, 2017). Staphylococcus succinus isolates from doenjang, a highsalt-fermented soybean product, did not exhibit hemolysis (Jeong et al, 2016a) and attempts to amplify enterotoxin genes were unsuccessful (unpublished results).…”
Section: Staphylococcus Succinusmentioning
confidence: 95%
“…Among them, strain 14BME20 was selected as a starter candidate. Genomic analysis confirmed that strain 14BME20 did not contain any of the known S. aureus virulence factor-encoding genes but did carry strain-specific genes for lipid degradation, which may contribute to the production of volatile compounds (Jeong and Lee, 2017 ).…”
Section: Safety Of Cns Derived From Fermented Foodsmentioning
confidence: 98%
See 1 more Smart Citation
“…To our knowledge, this is the first time S. succinus has been reported in duck meat fermentation processes, although it has been found in other fermented meat products before [ 42 , 61 ]. This is not necessarily a matter of concern, but some strains of S. succinus exhibit proteolytic, lipolytic, and urease activities and can also be hemolytic and toxigenic [ 62 , 63 ]. Further, one should be mindful of the shortcomings and limitations of culture-based methods as they cannot identify nonculturable cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. succinus strain 14BME20 (thereafter referred to as 14BME20) cleared the safety and functionality tests, and was selected as a potential starter culture candidate for soybean food fermentations. Furthermore, the complete genome sequence analysis of 14BME20 revealed that the strain does not encode any of the virulence factors found in the well-known pathogen Staphylococcus aureus (17).…”
Section: Introductionmentioning
confidence: 99%